Biocontrole com Trichoderma e Bacillus à Sclerotinia sclerotiorum na cultura da soja - Schmoller, Isabela (2021)
Soy is the main product of Brazilian agriculture, strengthening the country's position as one of the most important commodities in world agricultural trade. But there are numerous factors that affect its quality and productivity, including the incidence of diseases. White mold caused by the fungus Sclerotinia sclerotiorum (Lib) de Bary, also known as sclerotinia rot, has been highlighted as one of the most severe for the crop. There are no soybean cultivars resistant to S. sclerotiorum, and chemical control of white mold has limitations due to costs, loss of fungicide efficiency and difficulties in obtaining total plant protection during spraying. Therefore, practices such as cultural control with straw formation for the direct planting system and biological control with antagonists such as Trichoderma and Bacillus have been used in the management of the disease. The objective was to evaluate the effectiveness of biocontrol agents in the colonization of S. sclerotiorum sclerotia in the soil, under soybean cultivation. Two experiments were carried out in the agricultural years of 2019/2020 and 2020/2021 at the experimental station of the Federal Technological University of Paraná - UTFPR - Dois Vizinhos, the treatments being Trichoderma harzianum, isolated IBLF 006 (0.1kg/ha); Bacillus subtilis lineage QST 713(3liters/ha); and association Trichoderma harzianum, isolate URM 8119, Trichoderma asperellum, isolate URM 8120 and Bacillus amyloliquefaciens, isolate CCT 7901(0.1Kg/ha). The plant cover that preceded the soybean crop was Black Oat BRS 139, sown in the field and when it reached the phenological stage of full flowering, it was rolled, with the aid of a knife roller, and sowed soybean cultivar BRS 282. In the phenological stage V2 (two leaves true), samples containing 50 sclerotia were placed in 1.5 mm mesh nylon mesh bags and placed between the crop rows, being accommodated so that half of their height was below the soil surface. Two applications of biocontrol agents were carried out at stages V2 and V4 of the culture, respectively. The sprays were carried out with pressurized sprayers with CO2 with flow rates of 200 L ha-1. Twenty days after the last application of the biocontrols, the sclerotia were removed from the field and the carpogenic evaluation was carried out in the laboratory. The sclerotia were placed in a gerbox containing 200 g of autoclave, and then incubated at a temperature of 18ºC (±2ºC) and photoperiod (12 hours) for 20 days. In the carpogenic evaluation, the number of germinated sclerotia, number of apothecia per sclerotia, colonized sclerotia, degraded or rotten sclerotia and control levels were quantified. The results showed that in the two years of evaluations T. harzianum isolate URM 8119 and B. subtilis lineage QST 713 had a biocontrol effect on S. sclerotiorum, with control means of 36.4%, not differing from each other in terms of control efficiency. However, when the association of T. harzianum, isolate URM 8119, T.asperellum, isolate URM 8120 and B. amyloliquefaciens, isolate CCT 7901 was used, it showed greater efficiency in controlling S. sclerotiorum, with an average of 52.8%, proving that there was a synergism between biological agents.